Optimization of shrinkage porosity in AlSi5Cu1Mg alloy using response surface methodology. (2020) - Nagabhooshanam, N.; Nishanth, R.; Singh, R. Leo Bright; Austin, N.; Mohanavel, V.
Abstract: Casting of aluminium alloys with zero defects would be ultimate aim of any manufacturer. In this present study, an effective approach has been developed to describe the optimal condition identified to reduce the shrinkage porosity formation in AlSi5 Cu1 Mg alloy using Gravity Die Casting (GDC) process. Experiments were conducted by varying solidification time, metal temperature, pre-heat molten temperature using response surface methodology (RSM) based Box-Behnken Design (BBD). The results revealed that solidification time increases with increase in pouring metal temperature and decrease with pre heat temperature of the mould. Experiments were conducted in order to validate the theoretical approach. The predicted values from RSM based BBD with experimental data, was proposed that the developed method is useful and effective method to determine the optimized process conditions in GDC process.